High-density lipoprotein function is modulated by the SARS-CoV-2 spike protein in a lipid-type dependent manner - Correa, Yubexi (2023)
There is a close relationship between the SARS-CoV-2 virus and lipoproteins, in particular high-density lipoprotein (HDL). The severity of the coronavirus disease 2019 (COVID-19) is inversely correlated with HDL plasma levels. It is known that the SARS-CoV-2 spike (S) protein binds the HDL particle, probably depleting it of lipids and altering HDL function. Based on neutron reflectometry (NR) and the ability of HDL to efflux cholesterol from macrophages, we confirm these observations and further identify the preference of the S protein for specific lipids and the consequent effects on HDL function on lipid exchange ability. Moreover, the effect of the S protein on HDL function differs depending on the individuals lipid serum profile. Contrasting trends were observed for individuals presenting low triglycerides/high cholesterol serum levels (LTHC) compared to high triglycerides/high cholesterol (HTHC) or low triglycerides/low cholesterol serum levels (LTLC). Collectively, these results suggest that the S protein interacts with the HDL particle and, depending on the lipid profile of the infected individual, it impairs its function during COVID-19 infection, causing an imbalance in lipid metabolism.